Pore-water pressure accumulation during closely spaced earthquakes: Fundão Tailings Dam. Issue 1 (2nd January 2023) - Stark, Timothy D.; Lin, Jiale; Gimenes, Evandro de A.
ABSTRACT: This paper focuses on pore-water pressure accumulation in loose sandy tailings during three (3) earthquakes within four minutes and the accompanying decrease in effective stress to assess the dynamic stability of the Fundão Tailings Dam, which failed on 5 November 2015. Results of laboratory cyclic direct simple shear tests are used to illustrate the accumulation of pore-water pressures with closely spaced low-level cyclic events. The seismically-induced pore-water pressures in the loose sands below the left abutment downstream slope and setback area are used to estimate the decrease in factor of safety with time until failure occurred within 20–30 minutes of the earthquakes. Field cone penetration and standard penetration test conducted prior to the failure are used to calculate the factor of safety against liquefaction to estimate pore-water pressures generated during the fore, main, and aftershocks in the sandy tailings. The effective stress stability analyses utilise a liquefied shear strength ratio for the sand tailings below the left abutment downstream slope and toe of the plateau because the sand tailings reached the critical state condition due to a reduction in the effective stress. SITE LOCATION: 20.206500°S, 43.467111°W